The Relationship between Accounting Student Profiles and Knowledge and Skills in AI at Thai Private Universities - Ajoy , Shanu Chinnamma; Pachraponkamond, Sornzawand; Tridechapol, Naruemol; Lee, Punnut (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2022)
Due to the rapid digital disruptions change in the digital age through all professions. The accounting professions can be used as an example for those rapid digital disruptions change towards accounting education. The objective of this study was to study the relationship between accounting student profiles and their knowledge and skills in Artificial Intelligence (AI) by using the questionnaire as an instrument to collect the data from 249 undergraduate accounting students from 15 private universities in Thailand. The data analysis was mean, standard deviation, factor analysis, one-way ANOVA, and simple regression analysis. The results found that the year of study was related to student knowledge in AI, however; it was not found related to student skills in AI. The Grade Point Average (GPA) was related to student skills in AI, however; it was not found related to their knowledge in AI. However, the expected salary was related to both knowledge and skills in AI. This study was also confirmed a statistical significance relationship between accounting student knowledge in AI and their skills in AI. This study could be the guidelines for private universities, where offer the accounting degree, develop, train, and transform students to sustain in the rapid digital disruptions change in the digital age. Moreover, the private universities should concentrate on the technological change in order to face with digital disruptions change in the future.